2021
DOI: 10.1002/ptr.7082
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis and autophagy modulating dietary phytochemicals in cancer therapeutics: Current evidences and future perspectives

Abstract: The global incidence of cancer and cancer‐related mortality is expected to rise in recent years despite advancements in cancer diagnosis and therapeutics. Increasing evidences of decrypting molecular mechanisms underlying cancer progression have commanded the tremendous development of synthetic anticancer drugs. With limitations in the current conventional cancer therapeutic approaches, the non‐nutritive dietary phytochemicals have emerged as potent modulators of apoptosis and autophagy associated key signalin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 143 publications
1
31
0
1
Order By: Relevance
“…Apoptosis and autophagy are common types of programmed cell death, and their malfunction can contribute to tumor growth [8]. Autophagic cell death is mediated by the extensive degradation of organelles, which is dependent on autophagic flux [9].…”
Section: Introductionmentioning
confidence: 99%
“…Apoptosis and autophagy are common types of programmed cell death, and their malfunction can contribute to tumor growth [8]. Autophagic cell death is mediated by the extensive degradation of organelles, which is dependent on autophagic flux [9].…”
Section: Introductionmentioning
confidence: 99%
“…The results of this study showed that combinatorial treatment with cisplatin and MgCl 2 promoted LC3-II expression, suggesting that autophagy had been induced (Figure 3A, Supplementary Figure S6). However, it should be noted that autophagy has a dual role in malignant cells, serving as both a tumor suppressor and promoter in a context-dependent manner (Patra et al, 2021;Luo et al, 2021). Therefore, attempts should be made to utilize the anti-cancer role of autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, compounds like genistein, vanillin, hesperidin, eugenol, vinblastine, vincristine, orientin, and vicenin, ellagic acid, gallic acid, quercetin, trigonelline, myricetin, naringin, etc. exhibit potential antioxidant, anti-inflammatory, antiproliferative, anti-mutagenic, and radioprotective activities [ 9 , 24 , 36 , 37 ]. Therefore, diverse clinical trials and further characterization of these compound are of paramount importance so far as the translational value is concerned.…”
Section: Radiation Damage and Phytochemical Actionmentioning
confidence: 99%
“…Conversely, the inherent toxicity and high cost of synthetic r’ radioprotectors warrants the search for alternative radioprotective agents [ 8 ]. Recent reports have shown that naturally occurring compounds, especially phytochemicals, have the potential to modulate signaling pathways [ 9 , 10 , 11 , 12 ]. Several epidemiological studies have shown that the intake of some phytochemicals can exert effects on several signalling pathways and reduce the risk associated with radiation damage [ 13 ].…”
Section: Introductionmentioning
confidence: 99%